Resposta da batata cv. Cupido à fertilização organomineral - Santivañez Aguilar, Ariel (2016)
Potato crop cycle is relatively short and presents high yield per area; therefore, it is a very demanding culture for available nutrients in the soil solution. Despite its importance and the large number of studies about the crop, there is little research on plant nutrition regarding the use of organomineral fertilizer. This study evaluated potato, cv. Cupid, development and productivity as a function of fertilization with pelletized organomineral fertilizer. The experiment was done in Perdizes, Minas Gerais, in the rainy season of 2014/2015. The experimental design was a randomized blocks, with factorial arrangement of 4 x 2 (doses x management) and a control with mineral fertilizer, with 3 repetitions. Organomineral fertilizer doses were 25, 50, 75 and 100% of the conventional mineral dose, which was 600 kg ha-1 K2SO4, 850 kg ha-1 NH4H2PO4, and 300 kg ha-1 (NH4)2SO4 of topdressing 19 days after planting (DAP). Fertilization managements were with or without topdressing at 19 DAP, when the potato was hilled. Two plants per plot were sampled at 36, 50, 64 and 81 DAP and analyzed for leaf, stem and dry matter contents. DRIS - Diagnosis and Recommendation Integrated System was applied at 36 DAP and the potatoes were harvested 112 DAP and subjected to tuber classification. Throughout the cycle, stem, leaf and tuber dry mass showed no significant differences between the fertilization managements. The doses of organomineral fertilizer and topdressing management does not affect productivity, and the lower doses (25%) were similar the greater ones and the control, with an average of 16.8 t ha-1, demonstrating that it is viable to make a single application of organomineral fertilizer at planting due to operational efficiency. The low yields observed were due to high rainfall and temperature, creating favorable conditions for the incidence of pests and diseases. According to DRIS, the organomineral dose 75% for topdressing, presented the best nutritional balance.